2020
DOI: 10.1016/j.virusres.2020.198105
|View full text |Cite
|
Sign up to set email alerts
|

Host antiviral protein IFITM2 restricts pseudorabies virus replication

Abstract: Highlights Type I IFN and IFITMs showed marked upregulation following PRV infection in PK15 cells. IFITM proteins restricted PRV infection by interfering virus binding and entry. IFITM2-mediated inhibition of PRV entry requires the cholesterol pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Cellular RNA was isolated and reverse-transcribed to cDNA. Methods were performed as previously described [ 22 ]. Primers for RT-qPCR are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular RNA was isolated and reverse-transcribed to cDNA. Methods were performed as previously described [ 22 ]. Primers for RT-qPCR are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, IFN-inducible transmembrane proteins (IFITM1, 2, 3) are found to work as important host self-restriction factors, possessing a broad spectrum of antiviral effects. Xie et al IFITM2 are crucial for controlling PRV infection by interfering with cell binding and entry [ 94 ]. However, Wang et al found that knockdown of IFITM2 and IFITM3 expression don’t influence PRV infection.…”
Section: Prv Infection Inhibits Ifn Signaling Pathwaymentioning
confidence: 99%
“…Cellular RNA was isolated and reverse-transcribed to cDNA. Methods were performed as previously described (Xie et al, 2020). Primers for RT-qPCR are available upon request.…”
Section: Co-immunoprecipitation Assaymentioning
confidence: 99%